Atributos da qualidade de capacete para motociclista: a percepção dos profissionais motofretistas e mototaxistas - Neves, Flamarion (2011)
The purpose of this dissertation was doing a survey of perceptions of the professional motorcycle users about the quality of the product helmet as work equipment required. The study area was the city of Santa Maria RS, whose scenario mapped the profile and professional activity of the mototaxi e motofrete. The methodology applied in this thesis is exploratory purpose and quantitative nature, with a delineation of the survey used method, and is based on technical research in the analysis of statistical yearbooks on the evolution of the fleet of motorcycles, occurred between 2001 and 2010. The research was held in two steps. The first step deals with the theoretical, using the techniques of documentary and bibliographic study on standards and legislation of motorcycle helmets, and mapping the study area. The second step of the research refers to survey studies using 291 questionnaires of the representative sample of 1200 professionals, to understand the perception of satisfaction and importance on the uses and qualities of helmets. The result of this study showed that exist standards and Brazilian legislation that are in line with that recommend by the World Health Organization (WHO) and are aligned with international standards, as instruments those help to reduce the risks in traffic accidents. Identify that the professional activity with motorcycles and scooters is regulated by the federal law (Lei 12.009/2009), although it is not legal in the investigated area; show significant raise of the fleet of motorcycles in the last decade, contributing factor to modify the urban setting of Santa Maria RS, leading to a new profession known as motoboy ; reveal that this activity is structured in a informal relation, without employment, based on the flexibility and the inherent risk in the occupation; identified the drivers of other cars are the main cause of accidents involving motorcycles and, as a result of these accidents were the legs the most affected part, by the non-use of the protect equipment; in the other side, the head was the less affected, what was assigned to the use of the helmet; the visor was appointed as the helmet item that had the higher degree of insatisfaction, although was assigned as important. The research was guided by the focus on the user, appropriateness to the use , and showed the dimensions of quality in the order of satisfaction and importance attached to the helmet as: performance, comfort, durability, technical assistance and design, classifying them into equality of satisfaction and importance , except the items closures, accessories, ventilation, neck guard and visor.